IMPLEMENTASI PROGRAM SISTEM SIPIL DOYAN JALAN DALAM MEMBUAT INOVASI PELAYANAN KESEHATAN DI RUMAH SAKIT UMUM DAERAH KOJA JAKARTA UTARA PROVINSI DKI JAKARTA - idrus, iqbal aidar; Alfreyza, Naufal (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2020)
This study aims to determine how the Health Service Innovation Study of the Civil System of Doyan Jalan Koja General Hospital, North Jakarta. In this study using a qualitative research method or approach with descriptive research type. Researchers use method triangulation techniques so that the resulting data is more accurate and precise. Triangulation method, which is checking the use of the interview method is the same as the observation method, or whether the observation results match the information provided when the researcher conducts the interview. The results showed that the Health Service Innovation Study of Civil System Doyan Jalan General Hospital Koja, North Jakarta. This innovation has succeeded in cutting registration times, from 6 minutes to 20 seconds, and registration waiting time from 60 minutes to 5 minutes. This Doyan Jalan Civil Innovation uses information technology, for the flow of outpatient service processes in order to reduce patient queues. Then with the presence of this innovation, it has succeeded in cutting down several queuing counters which can now be done through an independent list booth machine where only one queue counter can be completed in the outpatient service list process. With this, it can be said that the innovation made by the Koja Regional General Hospital was successful and its effectiveness could be felt in the registration process for outpatient services in cutting down several counters so that it became more effective and faster in the process.